A new species of Tegenaria Latreille, 1804 (Araneae: Agelenidae) from western Iran - Zamani, Alireza; Marusik, Yuri M.; Malek-Hosseini, Mohammad Javad (Zootaxa, 2018)
Agelenidae is a species rich and globally-distributed spider family comprising 1274 species in 77 genera (World Spider Catalog 2018). In Iran, this family is currently represented by eight species in four genera (Zamani et al. 2018). Being the second largest genus of the family (after Draconarius Ovtchinnikov, 1999), Tegenaria Latreille, 1804, currently encompasses 105 species that are primarily distributed in the Palaearctic (World Spider Catalog 2018; Marusik & Zamani 2015). So far, four species of this genus are known from Iran: Tegenaria domestica (Clerck, 1758) (western, northern, central and eastern Iran), T. lenkoranica (Guseinov et al., 2005) (northern Iran), T. pagana C.L. Koch, 1840 (northern Iran), and the endemic T. zamanii Marusik et Omelko, 2014 (northern Iran) (Zamani et al. 2018). Two of these species, T. lenkoranica and T. zamanii have been reported from caves (Malek-Hosseini & Zamani 2017). Considering the lack of studies on this genus in Iran, many species are undoubtedly awaiting to be discovered. During the biospeleological investigations of Zagros Mountains, a new species of Tegenaria was collected in western Iran, which is described and illustrated in this paper. The specimens were photographed using an Olympus Camedia E-520 camera attached to an Olympus SZX16 stereomicroscope and digital images were prepared using “CombineZP” image stacking software. Leg ratios were measured on the dorsal side and all measurements are given in millimeters. Measurements of leg are listed as: total length (femur, patella, tibia, metatarsus, tarsus). Standard abbreviations were used for the eyes: AME, anterior median eyes; ALE, anterior lateral eyes; PME, posterior median eyes; PLE, posterior lateral eyes. The specimens will be deposited in the Manchester Museum of the University of Manchester (MMUE).